FT-IR Spectroscopic Study of Triethyl Phosphate Adsorption on FAU Type Zeolite - BARDAKCI, BELGiN; KAYA, NESLiHAN (Asian Journal of Chemistry, 2010)
The adsorption of triethyl phosphate on FAU type zeolite has been investigated by using FT-IR spectroscopy. Zeolites are a large and diverse class of volcanic aluminosilicate crystalline materials which have many useful applications. They are used in oil cracking, adsorption of nuclear waste as well as production of controlled-release fertilizers for agriculture, adsorption of ammonia and other odour-volatiles, as cation absorbers in household detergents, as molecular sieves and for many other uses. Zeolites, which are known by their porous structure, are used widely to remove pollutants from nature. In this point of view, zeolites are special type of mineral which is playing an increasing role to solve environmental problems. In this study, we used NaY and NaX zeolites as adsorbents. After adsorption process, characteristic wavenumbers of triethyl phosphate had been observed by FT-IR spectroscopy. Addition to that, elemental analysis results had been supported that adsorption occurred on zeolite surface.